Antimony-doped enhanced photoluminescence quantum yield in zero-dimensional lead-free metal halide Rb2CsBiCl6 crystals. Issue 23 (24th October 2022) - Jia, Zhen; Gong, Pifu; Zhao, Jing; Chen, Mingxing; Wang, Yonggang; Wang, Zhigang; Dong, Yan; Xia, Mingjun
Abstract : A lead-free, high stability, all-inorganic Rb2 CsBiCl6 single crystal with 0D structure was successfully grown. The introduction of Sb 3+ can effectively narrow the band gap, resulting in a strong broad yellow emission with a high PLQY of 45. Abstract : Zero-dimensional (0D) lead-free all-inorganic metal halides have emerged as next-generation photoluminescent (PL) materials in recent years because of their extraordinary PL properties, non-toxicity, and high stability. Herein, a green, high stability, all-inorganic Rb2 CsBiCl6 single crystal with 0D structure was grown as a new PL material. Strikingly, using the antimony doping strategy, the broad yellow emission of Rb2 CsBiCl6 was significantly enhanced due to the enhanced absorption in the UV region, and the PL quantum yield was increased from 1% to 45% at room temperature. Furthermore, the fluorescent mechanism was revealed by the combination of optical characterizations and first-principles calculations.